A market failure approach to linguistic justice. Issue 7 (9th August 2017) - Robichaud, David
ABSTRACT: This paper will consider language management from the perspective of efficiency, and will set the grounds for a new approach to linguistic justice: a market failure approach. The principle of efficiency emphasises the need to satisfy individuals' preferences in an optimal way. Applying this principle with regard to language would justify language rights in certain domains, but also justify an array of additional linguistic interventions, thus providing better collective results in terms of people's preference satisfaction. Starting from a laissez-faire situation of total linguistic freedom, the paper demonstrates that many 'market failures' exist and that these prevent the coincidence of equilibrium and optimality. Due to market failures in the linguistic domain, we cannot expect free rational linguistic choices to produce optimal collective results, and linguistic freedom often becomes linguistic free-riding. Therefore, the just way to satisfy people's linguistic preferences is not by allowing them full equal liberty to choose the language they prefer to learn, use or transmit without any constraint. In order to improve the outcomes, we can sometimes prohibit certain forms of behaviour, and also use incentives and disincentives to promote alternative, more desirable, behaviours, thus offering every individual a fair chance to realise his/her linguistic preferences.